A potential contribution of the less negatively charged cell wall to the high aluminum tolerance of Rhodotorula taiwanensis RS1. Issue 11 (8th September 2016) - Hu, Zhen Min; Zhao, Xue Qiang; Bao, Xue Min; Wang, Chao; Wang, Wei; Zheng, Lu; Lan, Ping; Shen, Ren Fang
Abstract: Rhodotorula taiwanensis RS1 (Rt) is a high‐aluminum (Al)‐tolerant yeast that can survive Al at concentrations up to 200 mM. In this study, we compared Rt with an Al‐sensitive congeneric strain, R. mucilaginosa AKU 4812 (Rm) and Al sensitive mutant 1 ( alsm1 ) of Rt, to explore the Al tolerance mechanisms of Rt. The growth of Rm was completely inhibited by 1 mM Al, but that of Rt was not inhibited until Al concentration was more than 70 mM. The growth of alsm1 was inhibited much more by 70 mM and 100 mM Al than that of Rt. Compared with Rm cells, Rt cells accumulated less Al in the cell wall and cytoplasm. A time‐course analysis showed that Al was absorbed by Rm cells much more rapidly than by Rt cells when exposed to the same Al concentration. Meanwhile, the Al content of alsm1 was higher than that of Rt. Although the cell wall of Rt was thicker than that of alsm1 and Rm under control and 0.1 mM Al, that of Rt was thinner than that of alsm1 under 70 mM Al despite that their cell walls were thickened. The alcian blue adsorption was lower and cell wall zeta‐potential was higher in Rt and alsm1 than in Rm, indicating a less negative charge of cell wall of Rt and alsm1 than that of Rm. Taken together, the less negatively charged cell wall of Rt may restrict the adsorption of cationic Al in cells, potentially contributing to its high Al tolerance. Copyright © 2016 John Wiley & Sons, Ltd.